Association between glycemic traits and melanoma: a mendelian randomization analysis - Zhang, Yun-Chao; Lu, Cen-Di; Li, Quan-Yao; Shi, Jin-Na; Shi, Jun; Yang, Min (Frontiers in Genetics, 2023)
The causation of Glycemic Traits and risks of Melanoma remains unknown. We used Mendelian Randomization (MR) to assess the links between Glycemic Traits and Melanoma.Pooled data from Genome-Wide Association Studies (GWAS) were utilized to examine the relationships that exist between Fasting Insulin (n=26), 2-hour Glucose (n=10), Fasting Glucose (n=47), HbA1c (n=68), and Type-2 Diabetes (n=105) and Melanoma. We evaluated the correlation of these variations with melanoma risk using Two-Samples MR.In the IVW model, Fasting Glucose (OR=0.99, 95%CI=0.993-0.998, P<0.05, IVW), Type-2 Diabetes (OR=0.998, 95%CI=0.998-0.999, P<0.01, IVW) and HbA1c (OR=0.19, 95%CI=0.0415-0.8788, P<0.05, IVW) was causally associated with a lower risk of Melanoma. In all models analyzed, there was no apparent causal relationship between Fasting Insulin and Melanoma risk. There was no obvious causal difference in the IVW analysis of 2-hour Glucose and Melanoma, but its P<0.05 in MR Egger (OR=0.99, 95%CI=0.9883-0.9984, P<0.05, MR Egger), and the direction was consistent in other MR analyses, suggesting that there may be a causal relationship.The results of this study suggest that a higher risk of Fasting Glucose, Type-2 Diabetes, 2-hour Glucose, and HbA1c may be associated with a lower risk of Melanoma. However, no causal relationship between fasting insulin and melanoma was found. These results suggest that pharmacological or lifestyle interventions that regulate plasma glucose levels in the body may be beneficial in the prevention of melanoma.